PERAN INTEGRATED REPORTING DAN MANAJEMEN LABA DALAM MEMODERASI HUBUNGAN COMBINED ASSURANCE DAN LIKUIDITAS PASAR MODAL - A’fina Lutfi Bawazier; Siti Mutmainah (Diponegoro Journal of Accounting, 2026)
Capital market liquidity is an important indicator in assessing the efficiency and quality of information in financial markets. A high level of liquidity reflects low information asymmetry and increased investor confidence in companies. One governance mechanism that is believed to be capable of increasing capital market liquidity is Combined Assurance. This study aims to analyze the effect of Combined Assurance on Capital Market Liquidity with Integrated Reporting and Earnings Management as moderating variables in companies listed on the LQ45 Index on the Indonesia Stock Exchange (IDX) for the period 2022–2024. This study uses a quantitative approach with secondary data obtained from companies’ Annual Reports and sustainability reports. The research sample consists of 32 companies with a total of 96 observations, and data were analyzed using multiple linear regression with Moderated Regression Analysis (MRA) through SPSS.The results indicate that Combined Assurance does not have a significant effect on capital market liquidity. In addition, Integrated Reporting and Earnings Management are not proven to moderate the relationship between Combined Assurance and capital market liquidity. However, profitability, as proxied by Return on Assets (ROA), shows a significant positive effect on capital market liquidity. These findings suggest that assurance mechanisms and the quality of corporate reporting have not yet become the primary factors influencing stock trading activity among LQ45 companies listed on the Indonesia Stock Exchange.